2020
DOI: 10.3390/nu12010154
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of New Cichoric Acid–Metal Complexes in Bacterial Strains, Yeast-Like Fungi, and Human Cell Cultures In Vitro

Abstract: Cichoric acid (CA) belongs to the group of polyphenols, which occurs in a variety of plant species and it is characterized by anticancer, antibacterial, and antiviral properties. Selected polyphenols have the ability to combine with metal ions to form chelate complexes that reveal greater biological activity than free compounds. In order to study possible antimicrobial and anticancer effect of CA and its complexes with copper(II)/zinc(II)/nickel(II)/cobalt(II) we decided to conduct cytotoxicity tests to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Additionally, other edible plants, including Ocimum basilicum , Lactuca sativa L., Taraxacum officinale , and Cichorium intybus were reported as sources of chicoric acid [ 40 ]. Chicoric acid showed multiple promising pharmacological applications, among which are the reduction of the viability of colon cancer HCT116 cells and antimicrobial and neuroprotective effects [ 41 , 42 , 43 ]. Regarding the neuroprotective effects, in silico predictions yielded by the bioinformatics platform ADMETPrediction, but also experimental data by Wang and colleagues [ 44 ], indicated the capability of chicoric acid to cross the blood brain barrier.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, other edible plants, including Ocimum basilicum , Lactuca sativa L., Taraxacum officinale , and Cichorium intybus were reported as sources of chicoric acid [ 40 ]. Chicoric acid showed multiple promising pharmacological applications, among which are the reduction of the viability of colon cancer HCT116 cells and antimicrobial and neuroprotective effects [ 41 , 42 , 43 ]. Regarding the neuroprotective effects, in silico predictions yielded by the bioinformatics platform ADMETPrediction, but also experimental data by Wang and colleagues [ 44 ], indicated the capability of chicoric acid to cross the blood brain barrier.…”
Section: Resultsmentioning
confidence: 99%
“…The changes in the molecular structure of CA ligand due to metal complexation cause differences in the biological activity of complexes. Already the literature data showed that complexation of cichoric acid with 3d-transition metals affected the microbiological and cytotoxic properties of the ligand [ 15 ]. FRAP, DPPH, CUPRAC tests and theoretical calculations have shown that complexation with metals such as Cu(II), Zn(II), Ni(II) and Co(II) changes the antioxidant properties of cichoric acid.…”
Section: Resultsmentioning
confidence: 99%
“…This plant contains a number of phenolic compounds and it is a rich source of cichoric acid. Many studies revealed that metal complexes with phenolic acids often show an increase in their antimicrobial activity [ 15 , 16 ]. Cu(II), Zn(II), Ni(II) and Co(II) complexes with cichoric acid have higher antimicrobial potential than ligand alone, which may also result from its greater absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial activity of LL against E. coli, P. fluorescens and B. subtilis was estimated using luminescence method (BacTiter-Glo™) and MTT assay. The details were described previously (Jabłońska-Trypuć et al 2019b ; 2020 ). The antimicrobial activity of tested LL was presented as a relative cell viability of E. coli , P. fluorescens and B. subtilis as compared to control untreated cells and expressed in percentage.…”
Section: Methodsmentioning
confidence: 99%